Antigua and Barbuda. Significant achievements 2021 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Antigua and Barbuda during 2021 are identified, with respect to the needs and interests of the country, strengthening issues of apiculture, sustainability, resilience to climate change, land use, food safety and innocuousness, and composting. Likewise, work was done on improving irrigation systems, communication services, mitigating the problems caused by COVID-19, in the production of Miel Campeche and Piña negra. Finally, work was done on the development of a mobile application (Hive Keep), to manage beekeeping production processes.